The analysis of Denotative and Connotative Meaning in Ariana Grande’s Song Lyrics: A Semantic Study - Desy Riana Pratiwi; Lia Maulia Indrayani; Ypsi Soeria Soemantri (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
The meaning in language is indeed diverse in types, one branch of linguistics that studies about meaning is semantic science. Semantic referred to as the study of meaning, this research aims to analyze denotative meanings and connotative meanings contained in song lyrics, an expression of one's feelings or ideas usually expressed through song lyrics. The song chosen for this research data is Ariana Grande's song entitled "God is a woman". This analysis used a qualitative descriptive method which is a method that aims to analyze everyday phenomena and analyze the use of words including finding meaning contained in song lyrics. To answer this analytical question, used the main theory from Geoffrey Leech about semantics. The results of this analysis are more connotative meanings compared to denotative meanings in Ariana Grande song lyrics, this study found three connotative meanings and two denotative meanings. The number of connotative meanings and denotative meanings is not too much different, but connotative meanings are more numerous because this song contains many meanings that are not actually.